AN EXTENSION OF SOME RESULTS DUE TO JARDEN (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
This paper defines some generalized Fibonacci and Lucas sequences which satisfy arbitrary order linear recurrence relations and which answer a problem posed by Jarden in 1966 about generalizing an elegant result for a connection between even and odd subscripted Fibonacci and Lucas numbers.